Chemical and biological aspects of extracts from medicinal plants with antidiabetic effects - Gushiken, Lucas F. [UNESP]; Beserra, Fernando P. [UNESP]; Rozza, Ariane L. [UNESP]; Bérgamo, Patrícia L. [UNESP]; Bérgamo, Danilo A. [UNESP]; Pellizzon, Cláudia H. [UNESP] (Raiya Academic International, 2016)
Diabetes mellitus is a chronic disease and a leading cause of death in western countries. Despite advancements in the clinical management of the disease, it is not possible to control the late complications of diabetes. The main characteristic feature of diabetes is hyperglycemia, which reflects the deterioration in the use of glucose due to a faulty or poor response to insulin secretion. Alloxan and streptozotocin (STZ) are the chemical tools that are most commonly used to study the disease in rodents. Many plant species have been used in ethnopharmacology or to treat experimentally symptoms of this disease. When evaluated pharmacologically, most of the plants employed as antidiabetic substances have been shown to exhibit hypoglycemic and antihyperglycemic activities, and to contain chemical constituents that may be used as new antidiabetic agents. There are many substances extracted from plants that offer antidiabetic potential, whereas others may result in hypoglycemia as a side effect due to their toxicity, particularly their hepatotoxicity. In this article we present an updated overview of the studies on extracts from medicinal plants, relating the mechanisms of action by which these substances act and the natural principles of antidiabetic activity.
Keywords: Antidiabetic substances; Betacell; Diabetic complications; Islet of Langerhans; Medicinal plants; Toxicity; Type 2 diabetes mellitus